Linguistic Realization of Concept of PATRIOTISM in Modern Russian Linguistic Consciousness (on Data of Associative Chain Experiment) - N. V. Nagovitsyna (Научный диалог)
The article presents the course and results of linguistic experimental study of the psychological reality of underlying representations about patriotism in the modern Russian linguistic consciousness, revealed by the author in previous studies of semantic content of the concept of PATRIOTISM according to the language. The aim of the study was to verify data obtained in the analysis of linguistic and textual material, and to clarify the peculiarities of linguistic realization of the concept of PATRIOTISM in the consciousness of modern Russian native speakers on the results of a chain associative experiment. The research material is the language data of associative experiment (associates of word-stimulus patriotism ), obtained by the author in the course of processing 100 profiles of the subjects. Methodological basis of research are the theoretical foundations and principles of analysis of “the language of national culture,” developed in modern Russian cultural linguistics in the framework of a cognitive-oriented anthropocentric paradigm of modern humanitarian knowledge. The study uses methods of modern conceptual analysis and the methodology of the associative chain experiment. The study has been verified and refined semantics of the concept of PATRIOTISM, including 17 cognitive characteristics in the national conceptual sphere at the present stage. Practical significance of the research is that the main results can be used in the creation of training and methodological support in teaching Russian as a foreign language, as well as in the practice of compiling dictionaries of a new type -- dictionaries of concepts and linguistic thesauri.